A chemical mixer with dark-green nails. (3rd June 2015) - Leung, Lawrence K; Harding, John
Abstract : Nails are integral extensions of the skin and they together form the largest organ of the human body. Changes in nail appearance can be due to external insults or internal pathologies, and nail signs have to be interpreted in light of a good history. We present an interesting case of a man who developed dark-green discolouration of his nails over a short period of time. His work as a chemical mixer rendered him susceptible to hazardous chemical exposure. A notification was filed and the local Occupational Health Department discovered insufficient protective gear and lack of protocols regarding hazards of isocyanate-based resin. The patient also reported washing utensils with bare hands. Based on the meniscal demarcation borders between the discoloured and normal areas, plus a positive bacterial culture from nail clippings, the final diagnosis of isocyanate-resin-induced onycholysis with secondary Pseudomonas infection remained as the most likely clinical diagnosis.